Ritual purity and the Dead Sea scrolls - Werrett, Ian C. (Studies on the texts of the desert of Judah, 2007)
As the comprehensive study on the concept of ritual purity in the Dead Sea Scrolls since the publication of the legal material from Qumran, this book offers an examination of the purity material from Qumran through a diachronic lens.